DARE Training: Teaching Educators How to Revise Internal Medicine Residency Lectures by Using an Anti-racism Framework - Amanda R. Jowell; Aisha K. James; Rashmi Jasrasaria; Michael S. Kelly; Madeleine I. Matthiesen; Darshali A. Vyas; Sherri-Ann M. B; Jessica A. Zeidman (Association of American Medical Colleges, 2023)
Introduction Systemic inequities and provider-held biases reinforce racism and further disparities in graduate medical education. We developed the Department of Medicine Anti-Racism and Equity Educational Initiative (DARE) to improve internal medicine residency conferences. We trained faculty and residents to serve as coaches to support other faculty in delivering lectures. The training leveraged a best-practices checklist to revise existing lectures. Methods We recruited internal medicine faculty and residents to serve as DARE coaches, who supported educators in improving lectures' anti-racism content. During the training, coaches watched a videotaped didactic presentation that we created about health equity and anti-racism frameworks. DARE coaches then participated in a workshop where they engaged in case-based learning and small-group discussion to apply the DARE best-practices checklist to sample lecture slides. To assess training effectiveness, coaches completed pre- and posttraining assessments in which they edited different sample lecture slides. Our training took 1 hour to complete. Results Thirty-four individuals completed DARE training. Following the training, the sample slides were significantly improved with respect to diversity of graphics (p < .001), discussion of research participant demographics (p < .001), and discussion of the impact of racism/bias on health disparities (p = .03). After DARE training, 23 of 24 participants (96%) endorsed feeling more prepared to bring an anti-racist framework to lectures and to support colleagues in doing the same. Discussion Training residents and faculty to use DARE principles in delivering internal medicine lectures is an innovative and effective way to integrate anti-racism into internal medicine residency conferences.